Values Of Character Education Children Aged 4-6 Years On The Banjar - Palenewen, Evie; Rozie, Fachrul (Sekolah Pascasarjana Universitas Negeri Jakarta, 2024)
This study aims to find out how the parenting of Banjar ethnic parents affects providing character education stimulation to children aged 4-5 years. This study employs a qualitative approach with ethnographic research (ethnographic approach). Ethnography is a type of assessment that is a way to express what the participants think and show the cultural meanings that the participants adhere to (Samiaji, 2012). Data collection techniques in this study were direct observation, unstructured direct interviews, and documentation. The participants in this study were 3 families with 4 children aged 4-6 years. The study's findings show that 1) forms of parenting for Banjarese parents in providing stimulation of character education to children aged 4-6 years at home, where parents play an important role in providing habituation or teachings of maritime people from the Banjar tribe and continuing them for children, such as worship and self-recitation, which include religious values, tolerance, and independence 2) Internalization of the values of religious character, tolerance, and independence has been well conveyed through parenting by Banjar tribe parents, namely producing children with noble character who hold on to religion.